Toba Ethnic Pangurason Tor-Tor Performance: A Study of Local Wisdom - Nurdiana, Putri; Siahaan, Jamorlan; Ginting, Rosita (Formosa Journal of Science and Technology, 2023)
In this research discusses the Toba Ethnic Tor-tor Pangurason Performance which is studied in the study of Local Wisdom. The problem in this research is the stages of movement and local wisdom values). This research aims to determine the stages of movement in the TorTor Pangurason performance and the local wisdom values contained in the Tor-tor Pangurason performance. The method used in analyzing this research problem is a qualitative method with field research techniques. There are (two) theories used in this research, namely Charles Sander Peirce's Semiotic Theory which is found in the stages, patterns, functions and meanings of the Tor-Tor Pangurason movement and Sibarani's theory of local wisdom (2012: 114). In the field of local wisdom, which contains the title "Tor-tor Pangurason Ethnic Toba Performance of Local Wisdom Studies" includes: Understanding the culture and natural conditions of a place or cultural preservation and creativity.